The morphologic and morphometric features of the pisiform: a radioanatomic study - Demirtas, İsmet; Ayran, Ayşegül; Verimli, Ural; Durmuş, Livan Gül; Buğdaycı, Onur; Bekiroğlu, Gülnaz Nural (Surgical and radiologic anatomy (English ed.), 2025)
Purpose The purpose of this study was to investigate the morphologic and morphometric features of the pisiform using various anatomical landmarks, and to analyze its topographic relationship with surrounding bony structures. Methods Unilateral CT images of the hand and wrist taken from 208 patients (62 females, 146 males) admitted to Radiology Department of Marmara University Faculty of Medicine between 2014 and 2019 retrospectively analyzed in the study. The mean age of the subjects was 33.4 (range, 14–65) years of age. Eight different measurements were performed using 3D Slicer software and one novel classification was made on the images of 117 (56.25%) right and 91 (43.75%) left hands taken in neutral position. The results were further compared between gender, laterality, and age groups. Results The mean values of the truncated hand length (THL), longitudinal diameter of pisiform (LDP), transverse diameter of pisiform (TDP), and piso-triquetral distance (PTD) were significantly higher for men than for women. No significant difference was found between the right and left side measurements. A significant difference was also observed in PTD values between the age groups. The novel classification used in the present study revealed that the most common shape of triquetral facet of the pisiform was ellipse type (85.6%), followed by round (10.1%), and cylindrical (4.3%) types, respectively. Conclusion The results of the study provide comprehensive morphologic and morphometric data for the pisiform and may lend support for better understanding of the region which would be beneficial for the surgical interventions of the hand and wrist.